Response of Soil Microbial Community Structure to Phosphate Fertilizer Reduction and Combinations of Microbial Fertilizer - Liu, Hang; Li, Songsong; Qiang, Ruowen; Lu, Enjia; Li, Cuilan; Zhang, Jinjing; Gao, Qiang (Frontiers in Environmental Science, 2022)
The excessive application of phosphorus (P) fertilizer is becoming a major agricultural problem, which is accompanied by the reduction of P fertilizer utilization rate and the degradation of soil quality. We explored the differences in soil properties, enzyme activities, bacterial community, and fungal community structure in maize under different P fertilizer reduction systems. The study included five treatments namely; (1) no P fertilizer (P0); (2) farmers’ traditional P fertilization scheme (FP, 120 kg/hm2 of P2O5 of diammonium phosphate as base fertilizer); (3) 30% reduction in P fertilizer application (P1, 84.0 kg P2O5/hm2 of microbial blended fertilizer as base fertilizer); (4) 30% reduction in P fertilizer application (P2, 67.2 kg P2O5/hm2 of microbial blend fertilizer as base fertilizer + 16.8 kg P2O5/hm2 of diammonium phosphate as starting fertilizer); (5) 30% reduction in P fertilizer application (P3, microbial inoculum seed dressing + 84.0 kg P2O5/hm2 of diammonium phosphate as base fertilizer). The treatments with P fertilizer reduction combined with microbial fertilizer significantly increased soil organic matter (SOM), total phosphorus (TP), available phosphorus (AP) available potassium (AK) contents, and acid phosphatase activity (ACP), however, soil urease activity was significantly reduced. Moreover, the treatments with P fertilizer reduction combined with microbial fertilizer altered soil bacterial and fungal community composition by significantly increasing the relative abundance of a potential beneficial genus (i.e., Bacillus, Pseudomonas, Penicillium, and Acremonium) and potentially pathogenic genus (i.e., Fusarium, Gibberella, and Drechslera). Soil bacterial and fungal communities between treatments with high-P and reduced-P systems formed different distributions, and AP was the main driving factor affecting the differences in bacterial and fungal community structures. The structural equation model (SEM) revealed that different P fertilizer reduction systems had significant indirect effects by pH, SOM, AP, AN, TP on bacterial community structure and significant indirect effects by pH, SOM, AN, TN on fungal community structure. The results suggested that the P fertilizer reduction combined with microbial fertilizer systems regulated the pathogenic and beneficial genus which created a microbial community that is favorable for maize growth. Moreover, the findings highlighted the importance of soil properties in shaping the soil bacterial and fungal community structure.